Factors Responsible for Utero-Vaginal Prolapse Among Women Attending at a District Hospital of Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background : Utero vaginal prolapse is a big health problem in Bangladesh. The aim of this study was to calculate prevalence of uterine prolapse and to find out the possible factors that are responsible for this disease among patients attended at Chattogram General Hospital (250 bedded) Bangladesh.Materials and methods: It was a descriptive study which was done between November 2016 to August 2017. This analysis was restricted to a sample that included all women complaints of uterine prolapse diagnosed and treated at Chattogram General Hospital.Results: During a 10 months period, 100 women were diagnosed and treated with uterine prolapse. The prevalence of utero-vaginal prolapse is 4.2%. The mean age at the time of clinical presentation was 40 years. In average, the women gave birth to four children vaginally. 20% of the women were smokers and 84% of them were postmenopausal. 10% of the affected patients had a Chronic Obstructive Pulmonary Disease (COPD) 41% suffered from hypertension and 15% had diabetes mellitus. The majority of the women with uterine prolapse reported that they were working heavily during perinatal period (78%).Conclusion : In this study several risk factors for uterine prolapse, specially extensive physical labor during pregnancy and immediately after delivery, 100% unavailability of skilled births attendants, smoking while having COPD and low food adequacy during perinatal period are mainly responsible for this common disease.Chatt Maa Shi Hosp Med Coll J; Vol.18 (2); July 2019; Page 33-36